Macrophage-Released Pyrimidines Inhibit Gemcitabine Therapy in Pancreatic Cancer - Halbrook, Christopher J; Pontious, Corbin; Kovalenko, Ilya; Lapienyte, Laura; Dreyer, Stephan; Lee, Ho-Joon; Thurston, Galloway; Zhang, Yaqing; Lazarus, Jenny; Sajjakulnukit, Peter; Hong, Hanna S; Kremer, Daniel M; et al. (Cell metabolism, 2019)
Pancreatic ductal adenocarcinoma (PDA) is characterized by abundant infiltration of tumor-associated macrophages (TAMs). TAMs have been reported to drive resistance to gemcitabine, a frontline chemotherapy in PDA, though the mechanism of this resistance remains unclear. Profiling metabolite exchange, we demonstrate that macrophages programmed by PDA cells release a spectrum of pyrimidine species. These include deoxycytidine, which inhibits gemcitabine through molecular competition at the level of drug uptake and metabolism. Accordingly, genetic or pharmacological depletion of TAMs in murine models of PDA sensitizes these tumors to gemcitabine. Consistent with this, patients with low macrophage burden demonstrate superior response to gemcitabine treatment. Together, these findings provide insights into the role of macrophages in pancreatic cancer therapy and have potential to inform the design of future treatments. Additionally, we report that pyrimidine release is a general function of alternatively activated macrophage cells, suggesting an unknown physiological role of pyrimidine exchange by immune cells.